RESPONSE TO DIRECT AND CORRELATED SELECTION ON YIELD AND LEAF BLIGHT IN CARROTS - Carvalho, Agnaldo Donizete Ferreira de; Silva, Giovani OlegÃ¡rio da (REVISTA DE AGRICULTURA, 2020)
This work aimed to estimate the genetic parameters and to verify the response to direct and correlated selection on yield and leaf blight components in carrot populations. The experiment was carried out in the experimental field of Embrapa Vegetables, from November 2010 to April 2011. Half-sib families of three carrot populations were sowed with a randomized block design with three replications and plots of 1.1 m2. Was evaluated the area under the disease progress curve and the marketable and total root mass. It was found that the population CNPH-561 presented the highest level of resistance to leaf blight, but lower genetic variability to obtain greater gains with the selection for this character. For all populations evaluated, selection for marketable root mass and total root mass would allow direct and indirect gains for these traits. Selection for leaf blight, whether direct or indirect, would be efficient only for the CNPH-587 population.